Combined change detection analysis of the impacts resulting from heavy rainfall events in mountainous areas - E. Matta; G. Nigrelli; W. Alberto; A. Filipello; M. Zittlau; M. Chiarle (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of pristine and citrate-coated zinc oxide nanoparticles on soil nitrogen cycling determined using multi-level assessment of enzyme activity, functional gene abundance and microbial community composition - Ahmed Hussain; Mohammad Jahid Hasan; Kiran Vadde; Akanksha Matta; Matthew Moreno; Esteban E. Ureña-Benavides; Vikram Kapoor (Environmental Science and Pollution Research, 2026)

A Framework to Investigate the Effects of Observation Error on Neural Network Predictions of Fish Age - Derek W. Chamberlin; Thomas E. Helser; John D. Brogan; Irina M. Benson; Jason Conner; Andrew T. Chin; Christopher M. Gburski; Mary Elizabeth Matta; Julie A. Pearce; Kali R. Stone; Todd T. TenBrink; Morgan B. Arrington (Fish and Fisheries, 2026)
Technological innovations for predicting fish age represent a paradigm shift from conventional age estimation methods used in fisheries science. Recently developed secondary methods rely on models trained on conventional age estimates, derived from subjective interpretation of growth patterns and a biological property of the fish to predict age. Hence, quantifying the error that propagates from these models and the conventional age estimates on which they are trained is critical to fully account for uncertainty in predicted ages used in fisheries stock assessments. We review the development of three secondary age prediction methods: image analysis, epigenetics and Fourier transform near‐infrared spectroscopy (FT‐NIRS); the use of artificial intelligence (AI) within each method; and present an approach to examine the effects of ageing error on AI age prediction models. As a case study, we conducted an empirical study, coupled with simulation, to quantify the effects of ageing error on the performance of a multimodal convolutional neural network (MMCNN) model used to predict eastern Bering Sea walleye pollock ( Gadus chalcogrammus ) ages from otoliths analysed using FT‐NIRS. Results indicated repeatability of predicted ages was high between instrument operators, while adding ageing error resulted in a slight decrease in model performance from R 2 = 0.92 and CV = 7.6% to R 2 = 0.87 and CV = 10.2% on test datasets. Our results also suggest the MMCNN model is robust to noise in calibration age data and model performance may be better than performance metrics indicate when the model is evaluated against data with increased error.

Exploring the Probiotic Potential and Immunomodulatory Capacity of Lactococcus lactis NCDO 2118 Against Bacterial Pathogens and Trypanosoma cruzi - Mariana Oliveira Silva; Malu Mateus Santos Obata; Rafael Obata Trevisan; Chamberttan Souza Desidério; Hugo Felix Perini; Weslley Guimarães Bovi; Isabella de Oliveira Ferrato Sousa; Isabela Sguilla Rotta; Marcela Fernandes da Matta; Julia de Moura Bernardi; Nadine Aparecida de Souza Benedito; Anna Victória Bernandes e Borges; et al. (Probiotics and Antimicrobial Proteins, 2026)

Changes in Body Size With Age Do Not Follow the Temperature‐Size Rule - Jennifer S. Bigman; Lewis A. K. Barnett; James T. Thorson; Sean C. Anderson; Krista B. Oke; Kelly A. Kearney; Darren J. Pilcher; Wei Cheng; Esther D. Goldstein; Mary E. Matta; Kirstin K. Holsman; Lauren A. Rogers (Global Ecology and Biogeography, 2026)
Aim The temperature‐size rule is often described as a reduction in ectothermic asymptotic or maximum body size with warming. Although this coincides with the expectation that faster growth under warming would lead to larger sizes early in life but smaller sizes later in life, there remain few tests of changes in size across ontogeny. Here, we use > 99,000 observations of weight‐at‐age of commercially important fishes over 25 years to ask whether changes in size across ontogeny can be explained by temperature. We also examine whether oxygen, a key part of a proposed mechanism behind the temperature‐size rule, explains patterns of weight‐at‐age better than temperature. Understanding how temperature and oxygen affect size across age offers a test of macroecological theory and can inform the future productivity of fisheries. Location Bering Sea, largest subarctic system (Latitude: 52° N–66° N, Longitude: 160° E–170° W). Time Period 1987–2023. Major Taxa Studied Commercially important fishes. Methods We coupled fisheries‐independent survey data and climate model output with spatiotemporal generalised linear mixed‐effects models, a novel framework for testing the temperature‐size rule. These models account for uneven sampling across space and time to assess long‐term trends, as well as the effects of temperature and oxygen on size across age. We additionally explore the effect of model structure on our results by comparing functional forms and how spatial and/or spatiotemporal random effects are included. Results Weight‐at‐age was variable over time for all species with no long‐term trend. Temperature better explained this variability than oxygen, but effects were small and not age‐specific, counter to the temperature‐size rule. Our results were sensitive to model structure as models with shared spatial effects across ages appeared to support temperature‐size rule predictions, but this support reflected spatial autocorrelation in size rather than age‐specific temperature responses. Collectively, this work shows that support for the temperature‐size rule in these fishes was an artifact of spatial patterns in size and growth. Main Conclusions Our work tests macroecological theory using nearly complete body size trajectories to understand not only changes in adult stages but how size changes across age. We highlight that relationships among size, growth, temperature, and oxygen are not as straightforward as theory suggests and illustrate that modelling decisions can have a large effect on tests of ecological theory, and more broadly, our ability to understand biological responses to climate change.

Decoupled responses of mycorrhizal fungal communities and function to recurrent wildfire - Solomon Maerowitz-McMahan; Christopher E. Gordon; Rachael H. Nolan; Pushpinder Matta; Amaia Montalban de la Mata; Jeff R. Powell (Soil Biology and Biochemistry, 2026)

Unraveling the synergy between electrical control strategies and scalability parameters on electrocoagulation performance for treating chromium-containing wastewater - Muhammad Zakaria; Minerva E. Matta; Safwat M. Safwat (Process Safety and Environmental Protection, 2026)

Retrieval of snow liquid water content from radiative transfer model, field data and PRISMA satellite data - C. Ravasio; R. Garzonio; B. Di Mauro; E. Matta; C. Giardino; M. Pepe; E. Cremonese; P. Pogliotti; C. Marin; R. Colombo (Remote Sensing of Environment, 2024)

Finding a needle in a haystack: DNA Haemoproteus columbae enrichment using percoll density gradient and flow cytometry - Brayan Andrés Gamboa-Suárez; Ingrid Astrid Lotta-Arévalo; Felipe Sarmiento-Salazar; Nubia E. Matta (Veterinary Parasitology, 2024)

Dual-chamber microbial fuel cells as biosensors for the toxicity detection of benzene, phenol, chromium, and copper in wastewater: Applicability investigation, effect of various catholyte solutions, and life cycle assessment - Safwat M. Safwat; Abdallah Khaled; Abdelsalam Elawwad; Minerva E. Matta (Process Safety and Environmental Protection, 2023)

Nickel removal from wastewater using electrocoagulation process with zinc electrodes under various operating conditions: performance investigation, mechanism exploration, and cost analysis - Omar A. Shaker; Safwat M. Safwat; Minerva E. Matta (Environmental Science and Pollution Research, 2022)
Economically feasible approaches are needed for wastewater treatment. Electrocoagulation (EC) is an electrochemical treatment method that removes various pollutants from wastewater. It has grown in popularity over conventional treatment methods, especially in industrial wastewater, due to its high performance and the ability to remove toxic compounds. However, it is crucial to reduce the costs associated with EC for widespread implementation. It is also important to decrease nickel (Ni) concentrations in wastewater to prevent potential health and environmental problems. Therefore, this study investigates Ni removal from synthetic and real wastewater using electrocoagulation. Zinc, as a novel electrode, was used as the sacrificial anode. Several operating conditions were assessed, including current density, initial pH, electrolysis time, and spacing between electrodes. The maximum Ni removal efficiency, after 90 min, reached 99.9% at a current density of 10 mA/cm 2 when the pH was 9.2 and the gap distance was 4 cm. The Ni removal rate reached 94.4% and 94.9% at a 2- and 6-cm spacing, respectively, after 90 min. Anode morphology, kinetic modeling, electrical energy consumption, and cost analysis were also investigated. The type of corrosion was uniform, which is easily predicted compared to pitting corrosion. The comparison between chemical coagulation and electrocoagulation was also reported. Experimental results indicated that the maximum Ni removal rates reached 99.89% after 90 min. The optimum spacing between electrodes was 4 cm, and the optimum current density was 10 mA/cm 2 . Additionally, the kinetic data were best represented through the second-order Lagergren model. The results demonstrated that the electrocoagulation performance was better than that of chemical coagulation for Ni removal. The maximum electrical energy consumption was 23.79 KWh/m 3 for Ni removal.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Delineation of the Genera Haemoproteus and Plasmodium Using RNA-Seq and Multi-gene Phylogenetics - Jasper Toscani Field; Josh Weinberg; Staffan Bensch; Nubia E. Matta; Gediminas Valkiūnas; Ravinder N. M. Sehgal (Journal of Molecular Evolution, 2018)

Intrinsic and environmental drivers of growth in an Alaskan rockfish: an otolith biochronology approach - Mary Elizabeth Matta; Thomas E. Helser; Bryan A. Black (Environmental Biology of Fishes, 2018)

Otolith biochronologies reveal latitudinal differences in growth of Bering Sea yellowfin sole Limanda aspera - Mary Elizabeth Matta; Thomas E. Helser; Bryan A. Black (Polar Biology, 2016)

High-resolution satellite turbidity and sea surface temperature observations of river plume interactions during a significant flood event - V. E. Brando; F. Braga; L. Zaggia; C. Giardino; M. Bresciani; E. Matta; D. Bellafiore; C. Ferrarin; F. Maicu; A. Benetazzo; D. Bonaldo; F. M. Falcieri; et al. (Ocean Science, 2015)
Sea surface temperature (SST) and turbidity (T) derived from Landsat 8 (L8) imagery were used to characterize river plumes in the northern Adriatic Sea (NAS) during a significant flood event in November 2014. Circulation patterns and sea surface salinity (SSS) from an operational coupled ocean-wave model supported the interpretation of the plumes' interaction with the receiving waters and among them. There was a good agreement of the SSS, T, and SST fields at the sub-mesoscale and mesoscale delineation of the major river plumes. L8 30 m resolution also enabled the description of smaller plume structures. The different plumes' reflectance spectra were related to the lithological fingerprint of the sediments in the river catchments. Sharp fronts in T and SST delimited each single river plume. The isotherms and turbidity isolines' coupling varied among the plumes due to differences in particle loads and surface temperatures in the discharged waters. The surface expressions of all the river plumes occurring in NAS were classified based on the occurrence of the plume dynamical regions in the L8 30 m resolution imagery.

Reproductive biology of the Alaska skate Bathyraja parmifera , with comments on an intersexual individual - M. E. Matta (Journal of Fish Biology, 2015)
A total of 1357 specimens of Alaska skate Bathyraja parmifera were collected in the eastern Bering Sea by fisheries observers and during scientific groundfish surveys from 2003 to 2005. Male and female gonads were examined for maturity stage and seasonal reproductive timing. Based on seasonal reproductive data, including the occurrence of egg cases, ovum size, ovum number, shell‐gland width and gonado‐somatic index, this species appears to reproduce continually throughout the year. Potential effects of maternal size upon the size and number of mature oocytes were also investigated, with total length having a significant, although weak, influence on both. Morphology of a single intersexual individual encountered during the collection period is also described.

The Relationship Between Ovarioles Number and Female Size in Blackflies of the High Andes of Colombia - L A Esquivel; L I Moncada; C A Panza; I G Camacho; F A Colorado; N E Matta (Neotropical Entomology, 2015)

Overexpression of α2,3sialyl T-antigen in breast cancer determined by miniaturized glycosyltransferase assays and confirmed using tissue microarray immunohistochemical analysis - Shilpa A. Patil; Wiam Bshara; Carl Morrison; E. V. Chandrasekaran; Khushi L. Matta; Sriram Neelamegham (Glycoconjugate Journal, 2014)

Otolith biochronologies as multidecadal indicators of body size anomalies in yellowfin sole ( L imanda aspera ) - Bryan A. Black; Mary E. Matta; Thomas E. Helser; Thomas K. Wilderbuer (Fisheries Oceanography, 2013)
Dendrochronology (tree‐ring analysis) techniques have been increasingly applied to generate biochronologies from the otolith growth‐increment widths of marine and freshwater fish species. These time series strongly relate to instrumental climate records and are presumed to reflect interannual variability in mean fish condition or size. However, the relationship of these otolith chronologies to fish somatic growth has not been well described. Here, this issue was addressed using yellowfin sole ( L imanda aspera ) in the eastern B ering S ea, for which a 43‐yr otolith chronology was developed from 47 otoliths and compared with body size for 6943 individuals collected in 1987, 1994, and 1999 through 2006. Among several metrics of size normalized for age and sex, average body mass index (defined as weight/length) had the strongest relationship to the otolith chronology, especially when the chronology was averaged over the 5 yr preceding fish capture date ( R 2 = 0.88; P

Effect of Low-Temperature Storage on Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) - R J Silva; F J Cividanes; E C Pedroso; J C Barbosa; D H Matta; E T Correia; A K Otuka (Neotropical Entomology, 2013)

Fostering itself increases nicotine self-administration in young adult male rats - Emily E. Roguski; Hao Chen; Burt M. Sharp; Shannon G. Matta (Psychopharmacology, 2013)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Water production functions in kiwi - E. A. Holzapfel; R. Merino; M. A. Mariño; R. Matta (Irrigation Science, 2000)

Characterization of distinct Gal : 3-O-sulfotransferase activities in human tumor epithelial cell lines and of calf lymph node GlcNAc : 6-O-sulfotransferase activity - E. V. Chandrasekaran; Rakesh K. Jain; John M. Rhodes; Ram Chawda; Conrad Piskorz; Khushi L. Matta (Glycoconjugate Journal, 1999)

Synthesis of Gal-β-(1→4)-GlcNAc-β-(1→6)-[Gal-β- (1→3)]-GalNAc-α-OBn oligosaccharides bearing O-methyl or O-sulfo groups at C-3 of the Gal residue: specific acceptors for Gal: 3-O-sulfotransferases - Rakesh K. Jain; Conrad F. Piskorz; E. V. Chandrasekaran; Khushi L. Matta (Glycoconjugate Journal, 1998)